2017
DOI: 10.1136/bmjopen-2016-015002
|View full text |Cite
|
Sign up to set email alerts
|

What is the best analgesic option for patients presenting with renal colic to the emergency department? Protocol for a systematic review and meta-analysis

Abstract: IntroductionPatients with renal colic present to the emergency department in excruciating pain. There is variability in practice regarding the choice of initial analgesic to be used in renal colic. The aim of this article is to outline the protocol for review of the efficacy and safety of non-steroidal anti-inflammatory drugs (NSAIDs), opioids and paracetamol use in renal colic pain management.Methods and analysisThis is the protocol for a systematic review, comparing efficacy of NSAIDs, opioids and paracetamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…NSAIDs and opioids have been reported to be the main classes of drugs for pain relief in patients with renal colic. However, different side effects have been reported for these drugs (15). Moreover, evidence suggested that frequently use of KET is related to enhanced risk of gastrointestinal bleeding (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs and opioids have been reported to be the main classes of drugs for pain relief in patients with renal colic. However, different side effects have been reported for these drugs (15). Moreover, evidence suggested that frequently use of KET is related to enhanced risk of gastrointestinal bleeding (8).…”
Section: Discussionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) and opioids are commonly used as pain relievers in emergency department. However, both of these classes of drugs have many side effects (6). In a meta-analysis, NSAIDs were found to be as effective as different types of analgesic agents such as narcotics in treatment of acute renal colic (7).…”
Section: Introductionmentioning
confidence: 99%
“…Their use is also limited in patients with hepatic failure and chronic obstructive pulmonary disease 5 . Opioids the other analgesic option have a wide range of side effects, including nausea, vomiting, hypotension, sedation, dizziness, and even respiratory depression 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs), or less effective opioids, such as morphine (when NSAIDs [6] are ineffective or contraindicated), are generally prescribed for acute flank pain in urological disease. However, NSAID administration in late pregnancy is associated with severe adverse neonatal outcomes [7].…”
Section: Introductionmentioning
confidence: 99%